Integração dos actantes e seus modos de existência na promoção da segurança hídrica na cadeia do agronegócio da soja - Barros, Adriano Adriano David Monteiro de (2023)
The objective of the thesis is to characterize the integration of actants and their modes of existence, for the promotion of water security in the soy agribusiness chain. Therefore, the thesis seeks to fill in the gaps observed in the literature, regarding the relationship between the Actor-Network Theory (TAR), the Modes of Existence (ME) and organizational studies, in particular studies focused on Sustainability. It is argued that, to understand the agency and value of water in promoting water security, it is first necessary to analyze how the actors involved in the soy chain, the object of this thesis, interpret the concept of sustainability, as well as evaluate the importance of the actants and their modes of existence, especially the modes of Organization, Moral and Attachment, in the adoption of sustainable practices. Furthermore, identifying the main controversies on the issue of “water security” contributes to understanding not only the mapping, evolution, and monitoring of changes in the network. For that, qualitative research is applied in the soy agribusiness chain, in the western region of Bahia. The research, in general, is characterized by a qualitative, exploratory, descriptive and propositional study, with the organization of the data constituted by the triangulation process, characterized by document analysis, direct observation and interviews with the main participants of the soy chain and its data analysis, from the IRaMuTeQ software, using the similarity analysis, Reinert's method and lexicographical analysis. In addition to the aforementioned configuration, complementary, the research uses cartography of controversies, as a method of the Actor Network Theory. The empirical field of research shows a heterogeneous network, in which the various associations shape new structures dynamically. Furthermore, the understanding of sustainability is based on the economic dimension, as well as the term “resource” shapes the actions of the actants. Finally, controversies related to monitoring, charging, granting, as well as cooperation between the actors were analyzed and related to modes of existence, making it possible to configure scripts, based on the Sustainable Product-Service System and aimed at promoting Water Security. Thus, the study strongly suggests that it is necessary to think of water not only as a resource at disposal, but as a value complex, as it is through dialogue, scripts, cooperation, and respect for the most varied modes of existence of the actants, that the actions targeted at water security will be effective.